САНАЦІЯ ПІДПРИЄМСТВА ЯК ДІЄВИЙ МЕХАНІЗМ ФІНАНСОВОЇ СТАБІЛІЗАЦІЇ ЙОГО ДІЯЛЬНОСТІ - Костецький, Володимир Володимирович (Науковий журнал «Світ фінансів», 2017)
Костецький В. В. Санація підприємства як дієвий механізм фінансової стабілізації його діяльності. Розкрито сутність санації та з’ясовано основні її характерні ознаки. Запропоновано визначати сутність санації за змістом, формою прояву, перспективною спрямованістю, обумовлюючими чинниками, джерелами фінансування. За допомогою наукових методів аналізу, синтезу і логічного узагальнення запропоновано власне визначення поняття “санація”. Розглянуто сутність організаційно-економічного механізму управління санацією підприємства, охарактеризовано його складові. Визначено основні інструменти організаційно-економічного механізму, що забезпечують ефективне управління санацією підприємства на основі формування санаційної стратегії. Запропоновано алгоритм запровадження механізму санації, що дозволить реалізувати та досягти його основної мети. Костецкий В. В. Санация предприятия как действенный механизм финансовой стабилизации его деятельности. Раскрыта сущность санации и выяснены основные ее характерные признаки. Предложено определять сущность санации по содержанию, форме проявления, перспективной направленности, обусловливающими факторами, сточниками финансирования. С помощью научных методов анализа, синтеза и логического обобщения предложено свое определение понятия “санация”. Рассмотрена сущность организационно-экономического механизма управления санацией предприятия, охарактеризованы его составляющие. Определены основные инструменты организационно-экономического механизма, которые обеспечивают эффективное управление санацией предприятия на основе формирования санационной стратегии. Предложен алгоритм внедрения механизма санации, которая позволит реализовать и достичь его основной цели. Kostetskyy V. Readjustment of enterprise as an effective mechanism for financial stabilization of its activities. Introduction. In a market economy readjustment of enterprises has significant economic potential, is an important instrument for regulating structural changes and is part of the most effective mechanisms for financial stabilization of enterprises. Purpose. Grounded theoretical and methodological foundations and practical recommendations for improving organizational and economic mechanism of reorganization of enterprises in the conditions of instability of the national economy. Results. The essence of readjustment on various aspects of the study including. A new approach in determining the nature of rehabilitation is getting functions readjustment of the position of macro and micro levels. The study found the main characteristics of rehabilitation as an economic category and asked to determine its nature in key areas: content, in the form of manifestation by promising direction for causing factors by source of funding. Using scientific methods of analysis, synthesis and logic synthesis proposed definition of “readjustment” The essence of the organizational and economic mechanism considered in the article and described his components. The basic tools of organizational and economic mechanism defined to ensure the effective management of readjustment on the basis of formation rehabilitation strategy. The algorithm implementation mechanism of reorganization proposed that will implement it and achieve the main goal of rehabilitation. Conclusion. Readjustment is successful when using internal and external sources of financial, organizational and production and technical improvements, the company is recovering from the crisis and ensure its profitability and competitiveness in the long run. However, the development of readjustment measures and finding sources of funding necessary to examine the specifics of the enterprise, take into account all internal and external factors affecting its activities. In determining the possible ways to finance anti-crisis measures at the enterprise must determine their relevance and flexibility, if the impact of unpredictable environmental factors.